Recent advances in the molecular design and applications of proteolysis targeting chimera-based multi-specific antiviral modality - Yang Zhou; Shujing Xu; Nerea López-Carrobles; Dang Ding; Xinyong Liu; Luis Menéndez-Arias; Peng Zhan (Acta Materia Medica, 2023)
Viral infections represent a major threat to human health and the global economy; however, most of the currently available antiviral drugs are not fully effective in restricting viral replication and selecting for drug-resistant variants. Targeted protein degradation technologies are promising strategies to avoid or delay the emergence of drug resistance. Among the protein degradation-based multi-specific approaches, proteolysis targeting chimera (PROTAC) is the main strategy applied in the antiviral field. In this review we will introduce the elements and mechanisms of action used by PROTAC technology, as well as the advantages of PROTACs over available antiviral drugs. We also summarize the latest progress in the application of PROTACs in antiviral research, discuss existing challenges and look into future opportunities for antiviral drug discovery.